1.58 rheumatoid factor binding is influenced by the N-Glycans of their IGG targets. (31st January 2014) - Magorivska, I; Jeremic, I; Herman, S; Munoz, L E; Bilyy, R; Herrmann, M
Abstract : Background and Objectives: In autoimmune conditions, like rheumatoid arthritis (RA), the own immune system attacks the body and causes inflammation. One of the consequences of inflammation during autoimmune diseases is a changed glycosylation profile of IgG antibodies. RA is not only characterised by an altered N-glycan structure bound to the Fc portion of IgG molecules but also by circulating rheumatoid factors (RF) that recognizes the Fc portion of IgG as antigen. The aim of our work was to investigate the glycosylation of immune complexes circulating in the blood of patients with seropositive and seronegative RA. Material and Methods: Sera from 70 patients with RA (RF positive n = 43 and RF negative n = 27) and 8 healthy donors (control) have been used in the analysis. (I) Random serum IgG-complexes were captured with F(ab')2 fragments of anti-human-IgG and analysed by ELISA for their interaction with anti-human-IgG, anti-human-IgM, AAL lectin (fucose-specific) and LCA lectin (manose-specific). (II) The IgG complexes eluted from the ELISA-plates were analysed by Western Blots for the presence of IgG, IgM and AAL as well as LCA binding. (III) IgG affinity purified with AAL-, SNA- and jacalin-agarose columns was tested by ELISA as target for IgM rheumatoid factor. Results: (I) The accessibility of fucose residues for the AAL lectin of circulating IgG complexes was much higher in patients with RA when compared to healthy donors. This reactivity was independent of the presence of IgM-RF. The accessibility of mannose residues for the LCA lectin of circulating IgG complexes was much higher in patients with RA when compared to healthy donors. This reactivity was only to be observed in the presence of IgM-RF. (II) Western Blot confirmed an increased presence of IgM in IgG complexes from seropositive patients with RA. The fucosylation of IgG did not differ much between all groups. (III) No difference was detected in IgM-RF affinity towards positive and negative fractions of AAL- and SNA-reactive IgG. However, IgM-RF displayed a reduced binding to the minor IgG fraction isolated with jacalin-affinity chromatography. Conclusion: In not-denatured IgG circulating in patients with RA the glycan shows a lower accessibility for the fucose-specific AAL lectin, independent of the presence of IgM-RF. In contrast, the increased binding of the LCA lectin is due to the presence of IgM complexed to IgG. IgM-RF did not discriminate between IgG reactive with AAL and SNA lectin. AAL – Aleuria aurantia lectin (α-1, 6 core fucose) LCA – Lens culimaris agglutinin (α-mannose) SNA - Sambucus nigra agglutinin (α-2, 6-sialic acid)